Education Briefing Property investment: portfolio modelling. Issue 2 (27th February 2023) - Patrick, Michael; French, Nick
Abstract : Purpose: The aim of this briefing is to look at the often overlooked impact of gearing (or leverage) on risk. The positive impact on equity return in a strong market is gained by increasing the overall risk of the investment and potentially negative impacts on returns in weak markets. Design/methodology/approach: This Education Briefing is an explanation of how the addition of individual assets to a portfolio can, with gearing, impact upon the portfolio risk/return profile. Findings: Through a simple example, this briefing shows how geared portfolios can struggle in poor markets when the servicing of the debt (at increased interest rates) can have a severe negative impact upon returns. Practical implications: The process of borrowing at a bank rate below the return rate on an investment project can increase the equity return of the project as long as all incomes and interest rate remain at appropriate levels but when incomes fall or disappear and/or interest rates rise, the implication for the assets return and/or solvency can be highly significant. Originality/value: This is a review of existing models.